Paul Gayler's sauce book 300 world sauces made simple - Gayler, Paul (Kyle Books, 2015)
Starting with French classics such as mayonnaise, hollandaise and veloute sauces, the author covers all the basics and then suggests variations such as adding orange to a hollandaise or olives to a bearnaise.